SPA KAKI DIABETIK DENGAN RENDAMAN AIR GARAM DAN MASASE DENGAN VIRGIN COCONUT OIL (VCO) EFEKTIF MEMPERBAIKI KELEMBABAN KULIT KAKI PADA DIABETESI - I Made Sukarja Sukarja (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2018)
Chronic hyperglycemia in diabetes mellitus triggers nonenzymatic glycosylation and excessive glucose to intracellular diffusion lead to structural abnormalities and capillary function and peripheral nerve injury. Nerve cell injury and supported by capillary dysfunction result in neuropathy. Autonomic neuropathy results in decreased skin moisture foot. Recovery of neuropathy is done by improving blood circulation and maintaining skin moisture foot. The purpose of this study was to determine the effect of diabetic foot spa on the sensation and moisture of the foot skin in diabetics. The study was conducted with pre test post test with control group design on 45 people divided into 25 people into treatment group and 20 people in the control group taken by simple random technique at Puskesmas II Denpasar Barat 2017. Treatment group was given treatment in the form of diabetic foot spa covers leg gym, foot soak and massage with VCO for 4 weeks, while control group get gymnastic of foot performed by puskesmas. Foot skin moisture was measured by skin moisture analyzer. The results showed that foot spas are more effective in improving foot moisture in people with diabetes. It is recommended that people with diabetes can do foot spa in the form of foot exercises, soak feet and dimasase with VCO regularly.